Recurrent atrial fibrillation predictors in patients with arterial hypertension: circadian heart rate variability analysis - D. V. Dedov; A. P. Ivanov; I. A. Elgardt (Кардиоваскулярная терапия и профилактика)
Aim. To identify the predictors of recurrent atrial fibrillation (AF) in patients with arterial fibrillation (AF), based on the analysis of circadian heart rate variability (HRV). Material and methods. The study included 62 patients with recurrent AF: 44 with AH (main group, MG) and 18 without AH (control group, CG). All participants underwent clinical examination, anamnestic assessment, Holter electrocardiography (ECG) with circadian HRV analysis, and echocardiography. Results. Based on the circadian HRV data, the predictors of recurrent AF in AH patients could include reduced range of cardiac intervals (up to 805,1 ms) and reduced standard deviation (<116,2 ms) among individuals with concentric left ventricular hypertrophy (LVH), as well as increased PNN50 >7,5 % and increased RMMSD >24,7 ms among individuals with eccentric LVH and LV dilatation. Conclusion. In AH patients with concentric LVH, recurrent AF is associated with increased sympathetic stimulation. As myocardial remodelling progresses, recurrent AF is linked to increased parasympathetic activation.